Islamic Family Law Reform in Indonesia (Typology, Revitalization, and Constitutional Challenges) - Moh. Mujibur Rohman; Nuri Wahda Salsabila Usmany; Bunyamin; Syamsul Bahri; Andi Nur Fikriana Aulia Raden (QISTHOSIA : Jurnal Syariah dan Hukum, 2026)
The reform of Islamic family law in Indonesia has been widely discussed; however, existing studies predominantly examine fragmented legal issues, historical developments, or specific statutory changes, leaving limited attention to the integrated relationship between reform typology, legal revitalization, and constitutional challenges. This study addresses this gap by analyzing how these three dimensions interact within Indonesia's plural legal system. Employing a normative juridical approach, the research examines constitutional provisions, legislation, judicial decisions, and relevant legal doctrines through statutory, conceptual, historical, and case analyses. The study aims to formulate a comprehensive framework for understanding the trajectory of Islamic family law reform and to assess its constitutional compatibility in promoting legal certainty, justice, and public welfare. The novelty of this research lies in the development of an integrative analytical model that connects the typology of legal reform with revitalization strategies and constitutional principles. The findings demonstrate that Islamic family law reform in Indonesia has evolved through adaptive, progressive, and accommodative patterns, reflecting dynamic interactions between Islamic legal values, national legal policies, and constitutional norms. Nevertheless, constitutional tensions remain regarding equality, human rights, and judicial interpretation. This research contributes to the discourse on Islamic legal reform by offering a constitutional perspective that supports the development of a more coherent, inclusive, and responsive family law system in Indonesia.